Misso Integral [holistic mission or the whole Gospel] applied: Brazilian evangelical models of holistic mission in the Arab-Muslim world - Edward L. Smither (Verbum et Ecclesia, 2011)
In this article, I will first show the historical development of this theological approach within the Brazilian and Latin American evangelical spheres through the work of the Latin American Theological Fraternity a movement founded in 1970 that maintained historic evangelical values (i.e. a high view of Scripture, the necessity of conversion) whilst also taking Latin Americas great social needs into account. Nurtured by thinkers such as Ren Padilla (Ecuador), Orlando Costas (Puerto Rico), Samuel Escobar (Peru), and later Valdir Steuernagel (Brazil), the movement has not only responded to the concerns raised by Liberation theologians, but it has also influenced the direction of the Lausanne Movement an expression of global evangelicalism. Secondly, I will discuss how misso integral has found its way into the missional bloodstream and become a central value for some Brazilian and Latin American missions organisations, including Misso Antioquia (1975) and PM International (1984). Finally, based on 55 interviews conducted in 20092010 with Brazilian workers and mission leaders focusing on the Arab world, I will show how Brazilian workers are demonstrating misso integral through their ministries and also why this approach is relevant in the Arab-Muslim world.